Technological innovation and economic performance - Steil, Benn; Victor, David G.; Nelson, Richard R. (Council on Foreign Relations books., 2002)
Information technology accounts for over one-third of recent U.S. GDP growth and nearly two-thirds of corporate capital investment. ''The New Economy'' appears omnipresent, but little is actually known about its workings.This seminal volume brings together the research and critical thinking of many of the world's top macro and micro economists to provide a unique, multifaceted perspective. Through the use of detailed, up-to-date country and industry studies, this book provides the most authoritative and detailed analysis ever assembled into the causes of technological innovation and its relationship to economic performance. The country studies cover the United States, Japan, Germany, France, the United Kingdom, and the Nordic states. Nine industry studies examine the Internet, computers and semiconductors, banking, securities trading, venture capital, energy, agricultural biotechnology, pharmaceutical biotechnology, and automobiles.Commissioned and brought together for the research project by the world-renowned Council on Foreign Relations, the authors have produced one of the most important compendia in applied economics to be published in recent times.The contributors are Charles Calomiris, Ian Domowitz, Robert Evenson, Charles Fine, Robert Gordon, Richard Langlois, Josh Lerner, Markku Malkamäki, Patrick Messerlin, Joel Mokyr, David Mowery, Richard R. Nelson, Stephen Nickell, Gary Pisano, Adam Posen, Daniel Raff, Horst Siebert, Timothy Simcoe, Benn Steil, Michael Stolpe, John Van Reenen, David Victor, and Matti Virén.